2006
DOI: 10.1103/physrevb.74.205412
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of Raman-active modes in linear and zigzag phases of fullerene peapods

Abstract: We report on minimum energy calculations, using a convenient Lennard-Jones expression of the van der Waals intermolecular potential, to derive the optimum configurations of C 60 molecules inside single wall carbon nanotubes. Depending on the diameter of the nanotube, C 60 molecules were found to form linear or zigzag chains inside the nanotubes. In the following, we use the spectral moments method, together with a bond-polarizability model, to calculate the nonresonant Raman spectrum for infinitely long isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 38 publications
7
27
1
Order By: Relevance
“…We observe that peapods in the tilted orientations and with angles greater than 40°[C 70 @ (12,9), C 70 @(13,8), C 70 @(17,3) ] have Raman spectra similar to those observed for standing orientations in the whole frequency range. The same observation can be performed between those with angles lower than 40°[ C 70 @(10,0) and C 70 @ (17,2)] and peapods in the lying orientations. Furthermore, an exchange in intensities is predicted for chiral peapods between the higher and lower components of the doublet located in the TLM range as the inclination θ varies.…”
Section: Resultssupporting
confidence: 68%
“…We observe that peapods in the tilted orientations and with angles greater than 40°[C 70 @ (12,9), C 70 @(13,8), C 70 @(17,3) ] have Raman spectra similar to those observed for standing orientations in the whole frequency range. The same observation can be performed between those with angles lower than 40°[ C 70 @(10,0) and C 70 @ (17,2)] and peapods in the lying orientations. Furthermore, an exchange in intensities is predicted for chiral peapods between the higher and lower components of the doublet located in the TLM range as the inclination θ varies.…”
Section: Resultssupporting
confidence: 68%
“…, is used to describe the Van Der Waals intertube interactions between the tubes in bundle, with parameters ε =2.964 meV and σ =0.3407 nm [19,30]. These values have recently been found to describe correctly the Van Der Waals contribution to the C60 bulk cohesive energy [27,28].…”
Section: Model and Methodsmentioning
confidence: 99%
“…Hodak and Girifalco showed that the guest molecules structure within the nanotube is diameter dependent [13,14]. Using a convenient Lennard-Jones expression of the van der Waals intermolecular potential to derive the optimum configurations of C 60 molecules inside single wall carbon nanotubes, Chadli et al have found that the C 60 molecules adopt a linear configuration with SWCNT diameters below 1.45 nm and a zigzag configuration for SWCNT diameters between 1.45 and 2.20 nm [15][16][17] (see Table 1). The optimum C 60 packing can be characterized by the angle formed by three consecutive C 60 (see Figure 2a).…”
Section: Peapodsmentioning
confidence: 99%